The LM-1030 Reading Strategies Course on the Spotlight - Ruiz Navarrete, Ronny (2013)
This exploratory study discusses several viewpoints regarding the structure and implementation of the course Reading Strategies I (LM-1030). The study presents a diagnostic inspection drawn from students enrolled in nineteen undergraduate programs where that reading course is mandatory. Essential aspects such as methodology, instructional materials, the students’ response to the reading program, and the course expectations in general are analyzed. Data was obtained from classroom observations, surveys and interviews.The results obtained reveal the strengths and weaknesses of the course and generate important implications and recommendations which may support informed decisions in the future.